Hospital humano: etnografia da humanização hospitalar na perspectiva de usuários - Gomes, Annatália Meneses de Amorim (2008)
This ethnographic work studies the experiences of patients admitted in public (PUH) and private (PRH) hospitals in the Brazilian northeastern region. 28 adult patients of different clinics participated in the study. Data were analyzed by the patient path method, consisting in a combination of complemented and articulated techniques free observation, participating observation, ethnographic interview and patient testimonials collected prospectively during the patients admissions, from their arrival and until their discharge. The analysis was carried out according to the Thematic Categories Analysis Technique and the data were interpreted pursuant to medical anthropology, healthcare humanization and healthcare promotion theoretical references. The ethical principles of Resolution 196/96 were followed. The human hospital, as revealed by the patient, highlights the significance of subjectivity. 225 (54.7%) out of 411 mentioned concepts were collected in a public hospital (PUH) and 186 (45.3%) in a private institution (PRH). The results show that the patient at the PUH and PRH ethnoevaluates different aspects of the healthcare professionals´ human and technical competence, the hospital´s functioning structure, the access to and the ethics in the financial management, and develops overcoming strategies for his stay at the hospital. This ethnoevaluation is mediated by different factors, namely: social and economic status, personality, religiosity, ironic speech, somber diagnosis and satisfied needs, prior hospital experiences and the conditions under which the interview was carried out. A pedagogic proposal for the hospital humanization must include structural, managerial and organizational changes of the offered services and use active methodologies aimed to the political resolution of problematic situations at work and the inclusion of affective and subjective factors, and become as well a tool for the collective learning. This study shows the importance for the user´s ethnoevaluation to be incorporated into the hospital management and care as a guideline in the decision making and clinical action, thus promoting practices that shall lead to a decent and humanized care. The multidisciplinary nature of this study allowed a wide understanding of the user´s perspective as a socially critical ethnoevaluator